Prevalência de anticorpos anti-Leptospira spp. em vacas nos municípios de Nova Guarita e Nova Santa Helena, Mato Grosso, Brasil - Santos, Rafael dos (2017)
Leptospirosis is a worldwide zoonosis that frequently affects domestic animals. In cattle the consequences of this infection are in the economic sphere. Losses are due to reproductive disorders such as abortions, increased embryonic mortality, stillbirths and temporary decrease in milk production. Serological investigations carried out in Brazil cattle evidenced as important the serovarity L. Hardjo, Wolffi, Pomona, Grippotyphosa, Icterohaemorrhagiae and Canicola. Until now, there weren’t few reports in the literature regarding the prevalence of the disease in cattle in the state of Mato Grosso, Brazil. This study proposal aims to determine the presence of antibodies anti-Leptospira spp. in cattle from the municipalities of Nova Guarita and Nova Santa Helena, Mato Grosso, Brazil. Blood samples were collected from 980 cattle from 49 farms, and samples were collected in a slaughterhouse located in the municipality of Sinop, Mato Grosso, Brazil. Of the 967 samples submitted to serological analysis, 174 were positive in the Microscopic Soroagglutination for Leptospira spp., determining a prevalence of 17.99% (95% CI = 15.69 - 20.54%), the prevalence observed among the municipalities Nova Guarita and Nova Santa Helena was 13.49% (95% CI = 12.81% - 14.16%) and 23.21% (95% CI = 22.04% - 24.37%), respectively. The prevalence of focus was 83.67% (95% CI = 79.48% - 87.85%). The most prevalent serovarity was the L. Wolffi 47.70%, followed by the serovarity L. Hardjo 16.10%; Bolivia 11%; Australis 7.47% Grippotyphosa 4.60%; Pomona 3.45%; Batavie 3.45%; Autumnalis 1.72%; Ichterohaemorrhagiae 1.72%; Hebdomadis 1.15%; Hardjo-bovis 1.15% and Castellonis 0.57%. It is concluded that infection by Leptospira spp. is endemic in the region, reiterating the need for new epidemiological studies in the state.